Effectiveness and safety of Ustekinumab for Crohn's disease; systematic review and pooled analysis of real-world evidence. Issue 9 (September 2019) - Engel, Tal; Yung, Diana E.; Ma, Christopher; Pariente, Benjamin; WIls, Pauline; Eliakim, Rami; Ungar, Bella; Ben-Horin, Shomron; Kopylov, Uri
Abstract: Background: Ustekinumab [UST] is effective in Crohn's disease (CD) in the UNITI studies. Several real-world experience (RWE) studies with UST have been published to date. Our aim was to summarize the available RWE data for UST effectiveness and safety. Methods: A systematic review of the available RWE studies of UST for CD and pooled analysis of the available effectiveness and safety data was performed. Results: Eight relevant studies of 6 RWE were included for analysis. Data from 578 patients were pooled for analysis. Most patients (97.7%) were anti-TNF experienced. Pooled clinical response rate was 60%, 62%, 49% at 12, 24 and 52 weeks respectively (95% CI (0.42–0.77), (0.48–0.75), (0.37–0.62)). Pooled remission rate was 39% (95% CI (0.18–0.65)) at 24 weeks and pooled endoscopic response rate was 63% (95% CI (0.53–0.72)) after approximately one year of UST; 134 adverse events (AE) were reported in total, pooled proportion 21% (95% CI (0.12–0.35)). Serious AE were reported in 19 patients, pooled proportion 5% (95% CI (0.03–0.08)). Infections were reported in 38, pooled proportion 6% (95% CI (0.04–0.11)). Conclusion: Pooled analysis of the RWE data suggests that the real-world effectiveness and safety are comparable to that reported in the randomized control trials.